Gender disparities in the STEM research enterprise in China - Kai Li; Xiang Zheng; Chaoqun Ni (Humanities & Social Sciences Communications)
Abstract Gender diversity is essential to the creation of high-quality research and scientific advances. This study provides a large-scale analysis of gender disparities in China’s scientific research enterprise, focusing on projects funded by the National Natural Science Foundation of China (NSFC) between 2010 and 2015. We inferred highly accurate researcher genders based on names in Chinese characters and matched them to their Chinese and English-language publications. We reveal a significant underrepresentation of women in both principal investigator (PI) roles and team participation. Women PIs led only 23.3% of NSFC-funded projects between 2010 and 2015 and accounted for 27.1% of authors on these project teams. Gender disparities were prominent across all fields, with the largest gaps in computer and engineering-related fields and the smallest in health and life sciences. Notably, the disparity intensified in more prestigious Key programs and senior scientist ranks, while Young scientist programs exhibited comparatively greater gender balance, suggesting potential benefits of targeted early-career funding policies. Women PIs tend to build a more gender-balanced team than men PIs, although both tend to recruit more men team members than women. Gender-diverse teams produced significantly more publications for both women and men PIs. These findings underscore the need for targeted policy interventions, including increased support for gender-diverse teams, institutional incentives for women leaders, and broader inclusivity initiatives to foster a sustainable and equitable scientific community in China.